Agenesis of the gallbladder and cystic duct - Waisberg, Jaques (2002)
Agenesis of the gallbladder and cystic duct is a rare anomaly that is usually asymptomatic. The patient may present symptoms characteristic of cholelithiasis. Its surgical confirmation requires careful dissection of the common bile duct and intraoperative cholangiography or ultrasonography to be performed, to exclude the possibility of an ectopic gallbladder. The authors describe two cases of this unusual affection and comment on its clinical, pathophysiological and diagnostic aspects.